Detection of Hydrogen Peroxide as a Potential Ros With Gold Nanoparticles and Copper (Ii) Chloride Catalyst - Fahim, Fuhad Hasan; Kabbo, Sumit Ghosh; Masud, Abdullah Al; Sanzida, Nahid (Chemical Engineering Research Bulletin, 2023)
Reactive oxygen species (ROS) play an important role in various biological processes including cellular signalling, oxidative stress, and disease development and thus accurate detection and quantification of ROS species is crucial for understanding their impact on biological systems and developing effective therapeutic strategies. H2O2 is one of the major ROS species. The objective of this study was to develop a cost effective, highly sensitive and selective H2O2 detection technique utilizing gold nanoparticles with cupric dichloride as a catalyst. Gold nanoparticles were synthesized by classical Turkevich method and UV-Vis spectrophotometer recorded the wavelength and absorption of surface plasmon resonance (SPR) peak. The structure and surface morphology of synthesized GNPs was obtained from SEM analysis and compared with literature values. Different amount of catalyst (CuCl2) was added to the reaction media and the shift in the absorption peak was recorded. This shift in the absorption peak was plotted against the concentration of hydrogen peroxide and it was observed that with increasing concentration of peroxide solution the shift in the peak also increases. Among the three different alternative amounts of CuCl2 (100μL, 200 μL and 300 μL), 100 μL catalyst in the reaction media was chosen as the best possible alternative. A calibration curve was generated by plotting the absorbance data against respective concentrations of H2O2 which successfully validated the goal of our work. Chemical Engineering Research Bulletin 23(2023): 22-25